Educational process improvement of oil and gas complex specialists training - Irina V. Vereshchagina; Svetlana A. Gulina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In this article problems of thermodynamic calculation of the driving gas-turbine engines working at natural gas are considered. The mathematical model of the accounting of heatphysical parameters of products of combustion of fuel gas is created, the algorithm of thermodynamic calculation with the exact accounting of change of heatphysical parameters of a working body for any composition of fuel gas is offered. The developed program of thermodynamic calculation of gas-turbine engines allows to carry out calculation of characteristics as again created engines, and engines which are in operation for the purpose of monitoring of change of characteristics of GTD during the work on gas fuel.